Metode Pengolahan Citra Untuk Mendeteksi Karies Gigi - Linda Wahyu Widianti; Sunny Arief Sudiro; Sarifuddin Madenda; Johan Harlan (Prosiding Seminar SeNTIK, 2018)
Metode Pengolahan Citra Untuk Mendeteksi Karies Gigi